Racial Segregation in Khaled Hosseini’s The Kite Runner and JM Coetzee’s Disgrace - Poudel, Ganga Ram (Kanya Journal, 2023)
This paper makes a comparative analysis of racial discrimination faced by the characters in the novels, The Kite Runner and Disgrace. Both novels are based on non-western settings and the characters become the victim of racial segregation. British rulers first promoted racial injustice in the process of expanding colonialism. As a result, racism emerged as a dominant factor of oppression of the people by power holders. Authors, in both novels, have shown their characters victimized by racial domination. In Hosseini’s The Kite Runner, the central character, Hassan becomes the victim of ethnic oppression as Amir and Assef dominate him and force Hassan and his father leave their home. Amir and Assef belong to Pashtuns and Hassan and his father belong to Hazaras in the Muslim community. They belong to different ethnic groups and the majority group dominates minority groups. Next, they become victims of Taliban oppression and are tortured and killed mercilessly. In Coetzee’s Disgrace, the central character, David Lurie as a white professor seduces his black student, Melanie Isaac, using his predominant racial power. Next, his daughter, Lucy is raped by three black men as a byproduct of the post-apartheid era. Racial attitude has created problems in the lives of the characters as they undergo many kinds of suffering in the novels. For analyzing the novels, racism has been used as a theoretical tool to explore the problems concerning human relationships. In The Kite Runner, there is the domination of one ethnic group over another ethnic group treating them as inferior and non-human. In Disgrace, there is the domination of whites over blacks and the domination of blacks over whites. Both novels reflect that racism based on any level is a social evil caused by human relationships and it has always negative effects on society. Due to racial segregation, one group dominates another group creating social problems.